Has the Data Efflux Regarding the Promising Outcome Following Injection of Deflux Changed the Management of Adult Vesicoureteral Reflux?. (10th March 2009) - Zilberman, D. E.; Mor, Y.
Abstract : Primary vesicoureteral reflux (VUR), traditionally considered a problem of childhood, can also be detected during adulthood. However, while the concept regarding the therapeutic management of VUR in children has undergone revolutionary changes, moving from surgical to conservative approach, the optimal therapeutic approach in adult reflux is poorly addressed and is still unknown. Herein, we review clinical and therapeutic approaches of VUR in pediatric population as published throughout the years. With the introduction of Deflux injection as a minimally invasive procedure, we identify a beginning of a new trend that further extends the indications for endoscopic injections, including its introduction to adult patients as well.